Run-Time and Statistical Pedestrian Level Wind Map for Downtown Toronto - Chen, Jiaxiang; Gianfelice, Michael; Izukawa, Nicole; Elshaer, Ahmed; Aboshosha, Haitham (Frontiers in Built Environment, 2021)
Rapid population growth and urbanization have led to the development of high-density and high-rise structures around the world. Tall structures in proximity can negatively affect pedestrian comfort by directing strong winds from the boundary layer (BL) to the ground near the structure. Pedestrian level wind (PLW) may affect local businesses/services, pedestrian comfort and in extreme cases jeopardizes pedestrian safety. The downtown portion of the City of Toronto (~10km2) was chosen as the study region due to the recent development of many high-rise structures. The region was split into 10 zones and Computational Fluid Dynamics (CFD) was utilized to study the wind effects of the local building geometry and arrangements. Wind velocities were extracted from CFD and coupled with historical meteorological data. The coupled velocities and wind bearings from CFD were found to be within 20% and 5% RMSE respectively of the recorded data at the wind station for 85% of the sampled data. Wind velocities were then extracted at various elevations and coupled with meteorological weather data to generate real-time, historical, and statistical visualization of local wind fields. This study enables prediction of real-time, historical, and statistical wind speeds, bearings at various elevations. Visualization of the flow field provides important insights for pedestrians, architects, engineers, and city planners regarding local wind speeds and identify problematic areas.